Effect of Extracted Titanium Tailing Slag on the Properties of Alkali-Activated Fly Ash-Ground Blast Furnace Slag Binder - Wang, Shuping; Li, Jingjing; Yun, Xiaoxin; Lv, Xuewei; Zhao, Yujie; Zhang, Zhigang (Frontiers in Materials, 2022)
The extracted titanium tailings slag (TS) is a by-product of titanium extraction from the blast furnace slag. Its chemical composition is similar to that of ground granulated blast furnace slag (GGBS), but the relatively lower reactivity limited its utilization as a supplementary cementitious material. In this study, the reactivity of TS was improved by mechanical grinding, and the optimum property of finely ground TS was selected to replace fly ash (FA) in the alkali- activated FA-GGBS binder. The influence of TS content on the fluidity, setting time and compressive strength of the ternary binder was investigated. XRD, FTIR and SEM were used to analyze the effect of TS on the reaction process. Results showed that the optimum reactivity index of TS was 81.18% at 28 days when it was ground for 15 min in a ball mill. The highest compressive strength of the alkali-activated ternary binder was achieved when the replacement of FA by ground TS was 40%, and its 28d compressive strength was 49.3 MPa, approximately 22% higher than the binder without TS. The addition of the TS would accelerate the reaction process of binder to form more products, including C-(A)-S-H and gismondine.